Development of a Canine Rigid Body Musculoskeletal Computer Model to Evaluate Gait - Brown, Nathan P.; Bertocci, Gina E.; States, Gregory J. R.; Levine, Gwendolyn J.; Levine, Jonathan M.; Howland, Dena R. (Frontiers in Bioengineering and Biotechnology, 2020)
Background: Kinematic and kinetic analysis have been used to gain an understanding of canine movement and joint loading during gait. Musculoskeletal models can further our understanding by non-invasively predicting muscle activation patterns and forces during gait. Methods: Pelvic limb kinematics and kinetics were measured for a 2 year old healthy female Dachshund (5.4 kg) during gait. A computed tomography scan was conducted to acquire pelvis and pelvic limb morphology. A bilateral pelvic limb subject-specific rigid body musculoskeletal computer model was developed in the OpenSim modeling platform to determine muscle activation patterns and forces during walking. Results: Gait kinematics determined from motion capture matched those predicted by the model, verifying model accuracy. Primary muscles involved in stance and swing were predicted by the model: At mid-stance the adductor magnus et brevis (peak activation 53.2%, peak force 64.7 N) extended the hip, and stifle flexor muscles (biceps femoris tibial and calcaneal portions) flexed the stifle. Countering vertical ground reaction forces, the iliopsoas (peak activation 37.9%, peak force 68.7 N) stabilized the hip in mid-stance, while the biceps femoris patellar portion stabilized the stifle in mid-stance and the plantar flexors (gastrocnemius and flexor digitorum muscles) stabilized the tarsal joint during early stance. Transitioning to swing, the iliopsoas, rectus femoris and tensor fascia lata flexed the hip, while in late swing the adductor magnus et brevis impeded further flexion as biceps femoris tibial and calcaneal portions stabilized the stifle for ground contact. Conclusions: The musculoskeletal computer model accurately replicated canine gait and was used to predict muscle activation patterns and forces. Musculoskeletal modeling allows for quantification of measures such as muscle forces that are difficult or impossible to measure in vivo.